Sets of orthoprojectors connected by correlations - Bespalov, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A problem of unitary classification of families of operators R_i=R_i^*=R_i^-1 in a Hilbert space, connected by some additional relations. Such families occur in problems concerning representations of a side class of *-algebras, among others, two parameter deformations U(su (2)), constructed by E. K. Sklyannyi.